Proton pump inhibitor associated hypomagnasaemia ‐ a cause for concern?. (25th January 2016) - Begley, Joe; Smith, Trevor; Barnett, Kirsty; Strike, Paul; Azim, Adnan; Spake, Claire; Richardson, Tristan
Abstract : Aims: In recent years, there have been a number of case reports of severe hypomagnesaemia associated with proton pump inhibitor (PPI) use, such that both the FDA and MHRA have issued drug safety warnings. They have recommended periodic serum magnesium testing in patients prescribed PPIs but provide no guidance on timing of these measurements. Methods: To our knowledge, we are the first to perform a prospective study to explore specifically proton pump inhibitor associated hypomagnesaemia (PPIAH). We followed 56 patients new to PPIs prospectively as well as a further 100 patients on long term PPIs cross‐sectionally to identify what factors may be influencing the development of significant hypomagnesaemia. Results: For the prospective arm of the study, we measured serum magnesium levels prior to starting a PPI and again at regular intervals for the next 8 months. For the cross‐sectional arm of the study we measured serum magnesium levels on patients on PPI therapy ranging from less than 1 year to over 5 years. Conclusion: We found that, although there was a significant downward trend in serum magnesium levels in patients new to PPI therapy with time, clinically relevant hypomagnesaemia was not readily identifiable on regular blood testing. We did however identify patients on concurrent diuretic therapy as being at higher risk and so would recommend regular serum magnesium testing alongside their regular renal function monitoring on a more frequent basis such as annually.